2021
DOI: 10.3389/fimmu.2021.676702
|View full text |Cite
|
Sign up to set email alerts
|

PTX3 Regulation of Inflammation, Hemostatic Response, Tissue Repair, and Resolution of Fibrosis Favors a Role in Limiting Idiopathic Pulmonary Fibrosis

Abstract: PTX3 is a soluble pattern recognition molecule (PRM) belonging to the humoral innate immune system, rapidly produced at inflammatory sites by phagocytes and stromal cells in response to infection or tissue injury. PTX3 interacts with microbial moieties and selected pathogens, with molecules of the complement and hemostatic systems, and with extracellular matrix (ECM) components. In wound sites, PTX3 interacts with fibrin and plasminogen and favors a timely removal of fibrin-rich ECM for an efficient tissue rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…Increased protease (MMP/TIMP) and PTX3 expression was found in LM-MSCs and BMSCs compared to LM cells in RNA-Seq, which was further confirmed by RT-PCR assays ( Supplementary Figure S7 ). Upregulation of these genes may be involved in the migration, invasion, ECM remodeling, and angiogenesis properties of LM-MSCs ( Lu et al, 2010 ; Cappuzzello et al, 2016 ; Doni et al, 2021 ). In addition, RNA-Seq data indicated that LM-MSCs highly expressed HOX9-13 genes, which was consistent with the qRT-PCR results described above ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…Increased protease (MMP/TIMP) and PTX3 expression was found in LM-MSCs and BMSCs compared to LM cells in RNA-Seq, which was further confirmed by RT-PCR assays ( Supplementary Figure S7 ). Upregulation of these genes may be involved in the migration, invasion, ECM remodeling, and angiogenesis properties of LM-MSCs ( Lu et al, 2010 ; Cappuzzello et al, 2016 ; Doni et al, 2021 ). In addition, RNA-Seq data indicated that LM-MSCs highly expressed HOX9-13 genes, which was consistent with the qRT-PCR results described above ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…We next focused on the markers of the 3 dpa-specific cluster 5 to characterize its identity. This cluster is enriched with pro-regenerative ECM and related genes including pentraxin 3 long a ( ptx3a ), collagen type XII alpha 1b ( col12a1b ), myristoylated alanine-rich protein kinase C substrate b ( marcksb ), and fibronectin 1a ( fn1a ) (Figures 3E and S4) 41, 42, 43, 44, 45, 46, 47 . In addition to the injury-induced epicardial expression of fn1a that is required for heart regeneration 41 , collagen XII (Col XII) deposition was reported to be boosted in both the epicardium and wounded tissues after cryoinjury in zebrafish 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Col XII is also an axon growth-promoting ECM that helps zebrafish spinal cord regeneration 43, 44 . Ptx3 is a secreted humoral innate immunity factor that orchestrates inflammation and tissue repair 45 . Besides the interactions with pathogens and complement molecules, Ptx3 also interacts with ECM components, such as fibrin and plasminogen, to promote a timely removal of fibrotic ECM for efficient tissue repair 48, 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Pentraxin 3 (PTX3) is an acute phase protein and a key component of immune humoral immunity rapidly synthetized by different cell types in response to microbial infection, tissue damage and different soluble factors such as TNF-α and IL-1. For its actions, PTX3 can be considered a humoral pattern recognition molecule that provides defence against infection playing several function in tissue repair [ 37 ]. In COVID-19, PTX3 has been proposed as a biomarker able to predict mortality at 28 days [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%